Can cryptocurrencies fulfil the functions of money? - Ammous, Saifedean (2018)
This paper analyses the monetary characteristics of five cryptocurrencies to evaluate whether they can perform the functions of money. While all cryptocurrencies can theoretically and practically serve as a medium of exchange, they are unlikely to become common and liquid media of exchange unless they can illustrate utility in one of the other functions of money. Digital currencies’ rigidly inflexible supply and wildly fluctuating demand make them too unstable to be used as a unit of account for the foreseeable future. Of the five, only Bitcoin has the potential to serve as a store of value, due to its strict commitment to low supply growth, credibly backed by the network’s distributed protocol and credible demonstration of the absence of any authority capable of altering the supply schedule. Other cryptocurrencies’ centralized control, and use as tokens for specific applications make them unlikely to fulfil monetary functions.